Preharvest and postharvest factors influencing vitamin C content of horticultural crops - Lee, Seung K.; Kader, Adel A. (Postharvest biology and technology, 2000)
Vitamin C, including ascorbic acid and dehydroascorbic acid, is one of the most important nutritional quality factors in many horticultural crops and has many biological activities in the human body. The content of vitamin C in fruits and vegetables can be influenced by various factors such as genotypic differences, preharvest climatic conditions and cultural practices, maturity and harvesting methods, and postharvest handling procedures. The higher the intensity of light during the growing season, the greater is vitamin C content in plant tissues. Nitrogen fertilizers at high rates tend to decrease the vitamin C content in many fruits and vegetables. Vitamin C content of many crops can be increased with less frequent irrigation. Temperature management after harvest is the most important factor to maintain vitamin C of fruits and vegetables; losses are accelerated at higher temperatures and with longer storage durations. However, some chilling sensitive crops show more losses in vitamin C at lower temperatures. Conditions favorable to water loss after harvest result in a rapid loss of vitamin C especially in leafy vegetables. The retention of vitamin C is lowered by bruising, and other mechanical injuries, and by excessive trimming. Irradiation at low doses (1 kGy or lower) has no significant effects on vitamin C content of fruits and vegetables. The loss of vitamin C after harvest can be reduced by storing fruits and vegetables in reduced O 2 and/or up to 10% CO 2 atmospheres; higher CO 2 levels can accelerate vitamin C loss. Vitamin C of produce is also subject to degradation during processing and cooking. Electromagnetic energy seems to have advantages over conventional heating by reduction of process times, energy, and water usage. Blanching reduces the vitamin C content during processing, but limits further decreases during the frozen-storage of horticultural products.